US-MEXICAN RELATIONS: FROM NAFTA TO NAFTA 2:0 - T. V. Kashirina (Гуманитарные и юридические исследования, 2022)
The article is devoted to the problem of concluding the NAFTA agreement in the context of US-Mexican relations and its revision in 2018. The conclusion of the NAFTA agreement took place during the neoliberal reforms carried out in Mexico by Presidents Miguel de la Madrid (1982 – 1988), carlos Salinas de Gortari (1988 – 1994) and Ernest Zedillo (1994 – 2000), and implied the reduction of state regulation of the country’s economic sector, liberalization of banking and credit operations, as well as foreign economic sphere. Neoliberal reforms in Mexico were carried out in the spirit of the «Washington consensus» - economic policy, «economic recommendations», which the United States tried to extend to other states. During this period, branches of the American TNC «Maquiladoras» began to gain more and more weight in the economic life of Mexico. It is proved that the initial war gave an impetus to the development of production and export-oriented goods, but secured to a certain extent the dependent position of the country within the framework of the treaty. The treaty also significantly undermined the development of Mexico’s agricultural sector. But on the other hand, the treaty promoted the economic cooperation of its participants, foreign policy contacts, and the strengthening of diplomatic and social ties. During the election campaign of the future US President D.Trump presented the agreement in the context of the desire of the United States to withdraw from the free trade zone. In the spirit of protectionism, D. Trump believed that NAFTA led to the «overflow» of American production capacities, the deindustrialization of the country’s economic sector and the growth of the surplus in trade with the United States. The firm intentions of the US president to reform the agreement resulted in the reset of NAFTA. The renewal of the USMcA agreement in 2018 strengthened the access of American companies to the Mexican market, and especially to the oil-producing sphere. The new USMCA agreement regulates a wide range of economic areas: the automotive industry, wage issues and the labor market, intellectual property and electronic commerce, financial transactions, exchange rates, dairy agricultural products and dispute resolution issues.It is concluded that both the initial and subsequent versions of the NAFTA/USMcA agreement were more beneficial to the United States. But even for Mexico, despite the concessions made, the agreement is a factor in maintaining relations with Washington.The article is devoted to the problem of concluding the NAFTA agreement in the context of USMexican relations and its revision in 2018. It is proved that the initial version of NAFTA contributed to the recovery of Mexico from the economic crisis, but secured to a certain extent the country’s dependent position within the framework of the treaty. The renewal of the agreement in the USMcA format in 2018 strengthened the access of American companies to the Mexican market, and especially to the oil sector. It is concluded that both the initial and subsequent versions of the NAFTA/USMCA agreement were more beneficial to the United States. But for Mexico, despite the concessions made, the agreement is a factor in maintaining relations with Washington.